2022
DOI: 10.1097/rli.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Free-Breathing Low-Field MRI of the Lungs Detects Functional Alterations Associated With Persistent Symptoms After COVID-19 Infection

Abstract: Objectives: With the COVID-19 pandemic, repetitive lung examinations have become necessary to follow-up symptoms and associated alterations. Low-field MRI, benefiting from reduced susceptibility effects, is a promising alternative for lung imaging to limit radiations absorbed by patients during CT examinations, which also have limited capability to assess functional alterations. The aim of this investigative study was to explore the functional abnormalities that free-breathing 0.55 T MRI in combination with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…As previously mentioned, a limitation of this study was that only a single coronal slice was investigated for PRE-FUL analysis. The use of an isotropic 3D 27 or multi-slice 2D PREFUL MRI [21][22][23][24][25] acquisition should help to improve repeatability by providing whole lung investigation of ventilation defects. Furthermore, the repeatability of PREFUL MRI may be limited by the seeded-region growing segmentation method that required some manual corrections.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, a limitation of this study was that only a single coronal slice was investigated for PRE-FUL analysis. The use of an isotropic 3D 27 or multi-slice 2D PREFUL MRI [21][22][23][24][25] acquisition should help to improve repeatability by providing whole lung investigation of ventilation defects. Furthermore, the repeatability of PREFUL MRI may be limited by the seeded-region growing segmentation method that required some manual corrections.…”
Section: F I G U R Ementioning
confidence: 99%
“…Postprocessing techniques such as Fourier decomposition, matrix pencil, self-gated non-contrast-enhanced functional lung, and phase-resolved functional lung (PREFUL) can generate ventilation-and perfusion-weighted maps of the lung based on free-breathing MRI data and have been used to assess lung function in a variety of pulmonary diseases. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Whereas other postprocessing methods can require extensive pulse sequence modifications, PREFUL MRI can be performed using a conventional spoiled gradient echo sequence, showing promise at both 1.5 and 3 T. PREFUL MRI also sorts images acquired during free breathing into complete respiratory cycles in the time domain, so both static and dynamic ventilation parameters, including regional ventilation (RVent) and flow-volume loops (FVL), can be obtained. Ventilation parameters derived from PREFUL MRI have been shown to correlate to PFTs and Xe-MRI in chronic obstructive pulmonary disease (COPD), CF, and health, 21 and can characterize the severity of coronavirus 2019 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Neben der Sauerstoffinhalation stehen in der Niederfeld-MRT noch die hyperpolarisierte Edelgas-Inhalation (Xenon 123 und Helium 3) und die Fourier-Dekompositions-MRT zur Verfügung. Letztere kommt sogar ohne intravenöses oder inhalatives Kontrastmittel aus 4 . Sollte es der Niederfeld-MRT gelingen die großen Hoffnungen in eine verbesserte Verfügbarkeit und kosteneffizientere Durchführung zu realisieren, bestehen gute Chancen die LAM und andere Lungenerkrankungen in Zukunft weiter multiparametrisch zu evaluieren und etablierte Erkenntnisse in den klinischen Alltag zu überführen.…”
Section: Studien-kommentarunclassified
“…PREFUL MRI 4 has been demonstrated to be sensitive for the early detection of abnormal ventilation dynamics in patients after lung transplantation 5 and in COVID-19 survivors. 6,7 In a recent study, dynamic ventilation parameters derived by PREFUL MRI were shown to depict the treatment response to indacaterol-glycopyrronium therapy in chronic obstructive pulmonary disease (COPD) patients. 8 These recent results emphasize the applicability of functional lung MR imaging for diagnosis and patient monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Proton magnetic resonance 3D phase‐resolved functional lung (PREFUL) 1 and other 3D lung MRI techniques 2,3 provide contrast‐free ventilation‐weighted whole lung imaging using dynamic data acquisition during free breathing. PREFUL MRI 4 has been demonstrated to be sensitive for the early detection of abnormal ventilation dynamics in patients after lung transplantation 5 and in COVID‐19 survivors 6,7 . In a recent study, dynamic ventilation parameters derived by PREFUL MRI were shown to depict the treatment response to indacaterol‐glycopyrronium therapy in chronic obstructive pulmonary disease (COPD) patients 8 .…”
Section: Introductionmentioning
confidence: 99%